Corporate Social Responsibility in Banking: Evaluating the Impact of CSR Practices on the Financial Performance of Selected Indian Banks - Bandna, Bandna; Ahmad Shah, Mushtaq; Hussain, Ilias; Gupta, Nitin; Hussain, Muzahid (Journal of Neonatal Surgery, 2025)
Corporate Social Responsibility (CSR) initiatives are primarily aimed at enhancing impact on society and the environment beyond its core business activities. These initiatives focus on various aspects such as poverty alleviation, healthcare, rural development, promoting financial literacy, education, and environmental protection. Despite the growing interest in CSR and its implications for businesses, there remains a need for empirical studies specifically focusing on the banking sector. This research aims to investigate how CSR practices impact the financial performance of banks. The study employs a causal and cross-sectional model to assess the influence of CSR activities on the financial performance of Indian banks. The findings reveal that banks prioritise community, environmental protection, and education in their CSR efforts, but their contributions to farmers' welfare and financial literacy are relatively limited. Additionally, the research highlights a notable difference in CSR practices between public and private sector banks. Furthermore, the study suggests that CSR performance has an impact on the financial performance of these banks. This study bridges the gap between CSR literature and financial performance in the banking industry by investigating how CSR practices influence profitability and investor decision-making in banks, giving insights that can nourish future studies and theoretical development. Banks can use the insights gathered to optimise their CSR efforts, better aligning them with financial objectives and improving overall performance. Investors may incorporate CSR issues into their decision-making processes, which may lead to better investment results and risk management. Regulators may use the data to create rules that encourage responsible banking and financial stability.